Analysis and enhancements to bollard designs - Yip, Kangli. (2009)
This final year project studied the vehicle and bollard collision process using finite element simulations. The type of bollard used in the simulations was the Land Transport Authority Type B concrete bollard on pavements in the civic district. The passenger car was modelled as a block of hollow high strength steel. When any of the finite elements in the bollard had a tensile stress of -25 x 106 Pa, failure in the form of element deletion would occur. For the finite elements of the passenger car, failure in the form of element deletion would occur when any of the elements had a strain of 0.12.